A medicina entre o concreto e o abstrato: consequências da exclusão do sujeito como exigência metodológica da medicina científica - Campos Neto, Milton Nuevo de (2015)
This research intended to study some aspects of medicine in its relation to modern science that enable a shift in the ultimate purpose of this (that we understand as: restore health to the patient). For this, we use a genealogical design, from Foucault , to articulate some incisive contributions of Canguilhem's work on this field. Along the way, we seek even by some contributions of Politzer and Lacan regarding the critique of modern science that we believe enriches our discussion. This study aimed to investigate the way in which medicine in their insertion in the field of modern science, performs a discursive maneuver that, by adopting the experimental method as royal road of research, submits itself to the cartesian distinction between subject and object. We conclude that such discursive maneuver allows that medicine look equate certain distinction of subjective and objective character (in the research circuit) to understand them, respectively, as abstract and concrete; this equivalence will be, then, the condition of possibility not only to the hegemony of a positivist perspective of research in medicine, but to the understanding of the pathological fact, once understood as pure empirical phenomenon, as something that can be studied in quantitative terms to the detriment of their qualitative character related to the experience of the subject who suffers. With this, introducing a discursive mode of production which seeks to raise the statistical knowledge (abstract) produced experimentally to the truth condition (concrete), which disqualifies absolutely the patient experience of suffering, alienating him from his condition in favor of acceptance of the medical knowledge, overlapping his own